Student Perceptions of Employer Use of Social Media in Selection Decisions: Comparing Criminal Justice Majors to Non-Majors. Issue 1 (2nd January 2020) - Rossler, Michael T.; Scheer, Charles
Abstract: An increasing concern among university professors and students alike is the image that students project through their social media accounts, particularly when future graduates seek employment in fields such as policing and other criminal justice careers. Despite this common concern, little research has examined the degree to which criminal justice (CJ) students accept employer use of social media searches as a screening tool, or whether there is variation among students based upon characteristics commonly associated with employment discrimination. Drawing upon a survey of over 630 students in criminal justice courses at five public universities, the current inquiry finds that criminal justice majors' opinions of social media searches do not differ from non-majors taking criminal justice courses. However, African-American, Latino, and students of other races all have less acceptance of the use of employer searches of social media than do white students. Implications for policy and future research are also discussed.